Sustainably Adjusting the Up-Conversion White-Emitting Luminescence Properties of GdAlO3: Er3+/Yb3+/Tm3+ Phosphors - Deng, Taoli; Jiang, Xianbang; Zhang, Qiuyun (Frontiers in Chemistry, 2020)
Doping heteroatom in phosphor can effectively improve the luminescent properties of phosphor, which has attracted great attention recently. GdAlO3 phosphors (GAP) doped with Er3+/Yb3+/Tm3+ were prepared via the co-precipitation method. Upon 980 nm excitation, strong blue, green and red upconversion (UC) emissions centered at 485, 525, 545 and 656 nm were observed, which could be successfully combined to form pure white light. It was found that changing the doping concentration of Er3+ and Yb3+ ions, the calcination temperature of the precursor, and the laser power of the excitation light source could systematically adjust the red/green/blue colors of GdAlO3:Er3+/Yb3+/Tm3+ phosphors to optimize the white emitting luminescence. When the Er3+ doping concentration increasing, each color distribution successfully moved, making the maximum shift of the CIE coordinate of the phosphors. Finally, the influence of each factor on adjusting the UC white light performance and its mechanism were explored.